The attitudes of pharmacists and physicians in Bosnia and Herzegovina towards adverse drug reaction reporting (Journal of Health Sciences, 2016)
Introduction: Adverse drug reactions (ADRs) are threat to the patient’s safety and the quality of life, and they increase the cost of health care. Spontaneous ADR reporting system mainly relies on physicians, but also pharmacists, nurses, and even patients. The aim of this study was to explore attitudes, barriers, and possible improvements to ADR reporting practices in Bosnia and Herzegovina.Methods: A self-reported questionnaire was developed to collect data on the perception of pharmacovigilance practice and ADR reporting. The survey was conducted in the period between September, 2014 and October, 2014.Results: The response rate was 73% (44 of 60) and 93% (148 of 160) among the pharmacist and family medicine physician groups, respectively. Regarding the attitudes to pharmacovigilance practice and reporting, both the pharmacists and physicians found the practices important. The majority of pharmacists and physicians in year 2014 did not report any ADR, while 18% of the pharmacists and 12% of the physicians, who participated in this study, reported one ADR. Reporting procedure, uncertainty, and their exposure were the main barriers to reporting ADRs for the pharmacists. The physicians claimed lack of knowledge to whom to report an ADR as the main barrier. A significant number of the respondents thought that additional education in ADR reporting would have a positive impact, and would increase the ADR reporting rate.Conclusions: Despite the overall positive attitude towards ADR reporting, the reporting rate in Bosnia and Herzegovina is still low. Different barriers to the ADR reporting have been identified, and there is also the need for improvements in the traditional education in this field.